Design of a Class AB Power Amplifier For 5G Applications - Joshua Aa-Daaryeb Nounyah; Bernice Ansu Pormaa; Emmanuel Mensah; Abdul-Rahman Ahmed; Raymond Gyaang (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
This work discusses the utilization of GaN HEMT technology on Rogers substrate in the design as well as the analysis of a 200 MHz Class AB power amplifier(PA)tailored for use in the 5G sub 6 GHz frequency band, specifically targeting 2.4 GHz applications.This is to satisfy the efficiency and linearityconstraints in typical 5G communications systems, especially at the input part of the communication chain,whiles realizing all round practical Figure of Merits (FoMs).Matching networks were devised employing cascaded L-section microstrip transmission lines, meticulously optimized foroptimum output power, return loss, and PAE. This demonstrates the effectiveness of the design approach in producing substantial power with heightened efficiency. Furthermore, the design exhibited enhanced linearity, even in the absence of commonly utilized feedback networks such as voltage dividers or emitter/source degenerationdue to the inherent robustness of the proposed design.The PA’s performance aligned exceptionally well with theoretical predictions. Electromagnetic simulation results showed a small signal gain of 13.634 dB with return losses maintaining below -12 dB across the desired operational bandwidth. Also, a power output of40.052 dBm for a 29 dBm input power was obtained, coupled with a PAE of 54.148%.